ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGGUNAAN APD OLEH PERAWAT DI PUSKESMAS RAWAT INAP BABAHROT KECAMATAN BABAHROT KABUPATEN ACEH BARAT DAYA PROVINSI ACEH TAHUN 2024 - ., Maisuri; kembaren, efrata; Sari, Nur Mala (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
Nurse compliance in using Personal Protective Equipment (PPE) is behavior as a professional regarding recommendations that must be carried out and obeyed according to procedures. The research is a quantitative analytical study using a cross sectional design. The aim of the research is to analyze the factors that influence compliance with the use of Personal Protective Equipment (PPE) by nurses at the Babahrot Inpatient Health Center, Aceh Regency. the population was 58 respondents in the Babahrot Inpatient Health Center, with total sampling technique, the data was obtained from the results of interviews by distributing questionnaires that had been prepared by the researcher. The Data analysis was carried out univariately and bivariately using an independent t-test with an alpha value (a) of 0.05. The results of the research were the influence of knowledge, attitudes, information about Personal Protective Equipment (PPE), availability of PPE, and supervision of compliance with the use of PPE at the Babahrot inpatient health center, Babahrot sub-district, last year. There was no effect of the work period on compliance with the use of (PPE) at the Babahrot inpatient health center, last year. There was no influence of education on compliance with the use of Personal Protective Equipment (PPE )at the Babahrot inpatient health center, Babahrot subdistrict,last year.